Perceptions of Non-Government Organisations Managers About International Financial Reporting Standards in NGOs Sector: A Case Study of a Large NGO in Durban, South Africa - Jean Damascene MVUNABANDI; Josue MBONIGABA (International Journal of Environmental, Sustainability, and Social Science, 2023)
The role of international financial reporting standards (IFRS) in the growth of organisations has expanded significantly in recent literature. Non-governmental organisations (NGOs) are crucial in global affairs and have different operating contexts, but it is unclear how their use of IFRS is of sufficient quality to satisfy various stakeholders' interests. On this question, this article investigated the managers' perceptions of IFRS practices and quality in a large NGO in Durban, South Africa. A qualitative approach was employed, and data was collected through semi-structured interviews with 24 purposively selected participants. The interviews were recorded and later transcribed. Robustness analysis was performed using conventional thematic content analysis. Evidence from this study showed that despite adopting IFRS accounting and financial procedures, the managers of the selected NGO found it difficult to have quality financial statements due to IFRS for SMEs failing to fit NGOs' operating context. This article established NGOs managers' perceptions of the role of IFRS in managing diverse NGOs stakeholders' interests, provided recommendations applicable to similar NGOs globally and contributed to the scholarly debates for policymakers and practitioners on using IFRS for SMEs in NGOs. This study has also provided a very robust plan for future researchers.